Leakage mechanism in AlxGa1−xN/GaN heterostructures with AlN interlayer. (1st January 2022) - Köhler, Klaus; Pletschen, Wilfried; Kirste, Lutz; Leone, Stefano; Müller, Stefan; Aidam, Rolf; Bronner, Wolfgang; Brückner, Peter; Waltereit, Patrick; Polyakov, Vladimir; Ambacher, Oliver
Abstract: Leakage of Al x Ga1− x N/GaN heterostructures was investigated by admittance–voltage profiling. Nominally undoped structures were grown by low-pressure metal-organic vapor-phase epitaxy. The investigated structures had an Al-content of 30%. They are compared to structures with an additional 1 nm thick AlN interlayer placed before the Al0.3 Ga0.7 N layer growth, originally to improve device performance. Conductance of field effect transistor devices with AlN interlayer, measured from depletion of the two-dimensional electron gas (2DEG) to zero volt bias at frequencies ranging from 50 Hz to 10 kHz, could be described by free charge carriers using a Drude model. The voltage dependent conductance shows a behavior described by either Poole-Frenkel emission or Schottky emission (SE). From the size of the conductance, as well as simulation of the tunneling current injected from the gate under off-state conditions by universal Schottky tunneling, SE is obvious. Evaluating the data by SE, we can locate the leakage path, of tens of nm in the range between gate and drain/source with contact to the 2DEG, originating from the AlN interlayer. The static dielectric constant in growth direction, necessary for the evaluation, is determined from various Al x Ga1− x N/GaN heterostructures to ϵ || (0) = 10.7 ± 0.1.